Investing in teaching development: navigating risk in a research intensive institution. Issue 3 (2nd July 2016) - Jawitz, Jeff; Perez, Teresa
Abstract : It is often assumed that academics working in a research intensive university are unlikely to invest in the professional development of their teaching. Institutional structures and culture tend to undermine investment in academics' teaching role. This study, conducted at the University of Cape Town, draws on an analysis of the environment within which academics make decisions to invest in their role as teachers. While acknowledging the privileging of research embedded in the institution, a significant group of academics have found ways to assert their academic identities as teachers despite the possible consequences and risks that this position entails.